ACEI and ARB continuation in the setting of noncardiac surgery. Issue 4 (April 2018) - Seehusen, Dean A.; Shahbodaghi, David S.
Abstract : N/A: Roshanov PS, Rochwerg B, Patel A, Salehian O, Duceppe E, Belley‐Côté EP, et al. Withholding versus continuing angiotensin‐converting enzyme inhibitors or angiotensin II receptor blockers before noncardiac surgery: an analysis of the vascular events in noncardiac surgery patients cohort evaluation prospective cohort. Anesthesiology . 2017; 126(1):16–27.